2010
DOI: 10.1021/es9031612
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene Photolysis in Aqueous Solution and Ice: Photon Flux Dependence and Comparison of Kinetics in Bulk Ice and at the Air−Ice Interface

Abstract: We report an investigation of the photolysis kinetics of polycyclic aromatic hydrocarbons (PAHs) in aqueous solution, frozen in ice, and at air-ice interfaces. Measurements of PAH photolysis rates in aqueous solution and at air-ice interfaces as a function of lamp power show that the kinetics depend nonlinearly on photon flux. In both media, the rates do not increase when lamp powers are above 0.1 W, which corresponds to total photon fluxes lower than 10(13) photon cm(-2) s(-1) in the actinic region. This sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 39 publications
8
86
5
Order By: Relevance
“…Those experiments indicated that the apparent reaction rate can be enhanced up to a factor of ten (Grannas et al, 2007a;Kahan and Donaldson, 2008;Weber et al, 2009;Kahan and Donaldson, 2010). Other chemical systems displayed similar apparent reaction rates in frozen and liquid samples (Dubowski and Hoffmann, 2000;Klánová et al, 2003a, b;Ružička et al, 2005;Matykiewiczová et Galbavy et al, 2010;Kahan et al, 2010c;Gao and Abbatt, 2011). In addition, a third kind of systems showed up to 10-times slower reactions in snow than in liquid samples for the same total concentration of reactants (Klánová et al, 2003a;Ružička et al, 2005;Matykiewiczová et al, 2007a;Anastasio and Chu, 2009;Bartels-Rausch et al, 2011;Gao and Abbatt, 2011).…”
Section: Chemical Processesmentioning
confidence: 86%
See 3 more Smart Citations
“…Those experiments indicated that the apparent reaction rate can be enhanced up to a factor of ten (Grannas et al, 2007a;Kahan and Donaldson, 2008;Weber et al, 2009;Kahan and Donaldson, 2010). Other chemical systems displayed similar apparent reaction rates in frozen and liquid samples (Dubowski and Hoffmann, 2000;Klánová et al, 2003a, b;Ružička et al, 2005;Matykiewiczová et Galbavy et al, 2010;Kahan et al, 2010c;Gao and Abbatt, 2011). In addition, a third kind of systems showed up to 10-times slower reactions in snow than in liquid samples for the same total concentration of reactants (Klánová et al, 2003a;Ružička et al, 2005;Matykiewiczová et al, 2007a;Anastasio and Chu, 2009;Bartels-Rausch et al, 2011;Gao and Abbatt, 2011).…”
Section: Chemical Processesmentioning
confidence: 86%
“…The faster loss of benzene and naphthalene are due at least in part to their aggregation to form dimers at ice surfaces, where they experience a redshift in the absorption spectra as compared to aqueous solutions, but aggregation does not explain the photolysis behaviour of anthracene and harmine at ice surfaces Kahan et al, 2010a). Under the same experimental conditions, anthracene photolysis in bulk ice proceeded at the same apparent rate as in aqueous solution (Kahan et al, 2010c). The observed rates did not depend on temperature in aqueous solutions (274-297 K) or at the ice surface (257-271 K) .…”
Section: Physical Environmentsmentioning
confidence: 97%
See 2 more Smart Citations
“…Some (but not all) of this increase may be attributed to spectral shifts giving rise to increased overlap with the excitation source Donaldson, 2007, 2010). The rate increase is clearly associated with compounds present in the interface region, as demonstrated by a rate increase as the surface/volume ratio of the ice sample is increased (Kahan et al, 2010c). Additionally, Kahan et al (2010a) showed that the rate of reaction could be "tuned" from that at the air-pure ice interface (fast) to that at the water interface (slow) by freezing salt water solutions of successively greater concentration.…”
Section: Photophysics and Photochemistrymentioning
confidence: 96%